Designing a multiepitope vaccine against toxoplasma gondii - Folasade, Hammed-Akanmu Mutiat (2021)
Toxoplasmosis is a significant, life-threatening disease with medical, veterinary, and economic importance caused by Toxoplasma gondii. T. gondii infects about 25-30% of human population globally. There have been noteworthy efforts to control and limit the disease incidence. At present, the only approved vaccine for use in veterinary is attenuated tachyzoites of strain S48 that control congenital infection of ewe known as Toxovax, which has significantly reduced the rate of abortion in sheep. However, the vaccine is expensive and has the probability of changing into a pathogenic form thus, it is inappropriate for human use. At the moment, there is no effective vaccine for preventing the formation of chronic tissue cysts in an infected host. Therefore, this research aims to design a multiepitope vaccine against T. gondii using in silico method to predict and analyze B-cell and T-cell epitopes of ROP2, MIC3, and GRA7. The result showed that the selected epitopes were antigenic, non-allergen, non-toxic, and non-human homology which makes them appropriate for the construction of vaccines. The secondary and tertiary structure, as well as the physiochemical properties of the vaccine construct, were determined and validation experiments such as molecular docking and immune simulation were conducted. This validation process predicted that the candidate vaccine is stable and soluble in the biological environment. In conclusion, in silico method can be used to design a good vaccine for T. gondii.